Estudio de factibilidad para la creación de una empresa comercializadora de productos naturales, homeopáticos y multivitamínicos en el Eje Cafetero. “Osli Ligth S.A.S” (2013)
The purpose of this project is to determine the feasibility study for making a new marketing business of natural homeopathic products and multivitamins (Osli light s.a.s) in Armenia , Quindio taking as reference the main growing consumption demand regarding these types of dietary supplements. The amount of potential buyers of natural homeopathic products and multivitamins is identified by the marketing study in pharmacies, health stores and doctors' offices that are located in the main cities of Eje Cafetero. To develop this study is important to have into account some variable like the analysis of demand and supply and the marketing behavior. Osli ligth s.a.s will be strategically located in Armenia to start an expansion process with different companies that demand this kind of complementary products, its logistic will be focused in the cafetera zone and later it will take into consideration different cities such Valle, Tolima and Cauca. On the other hand, define the horizons of the company is essential because it deals with the strategic development of its planning and organization system in which is defined the best method to guide the company towards its goal. . Osli ligth s.a.s Company is located in kioscos neighborhood block c number 24 in Armenia, Quindío. It is legally constituted and it counts with operating procedures which have to be with the company information and usage. Besides, the environmental impact is low because all waste, paper and other recyclable materials are going to be reused in order not to have adverse impacts and problems over time. To add, Osli ligth s.a.s Company in its first year of operation has some good strategies to organize the business. It invests in merchandise, sales and administrative expenses to ensure a successful start of operations, giving careful financial management for excellent profitability. Moreover, people that are involved have to control all the financial accounts to obtain a successful credit history to start future projects